Prosopis cineraria: A potential nootropic agent - Bithu B.S.; Ranga Reddy N.; Prasad S.K.; Sairam K.; Hemalatha S. (My University, 2025)
Context: Prosopis cineraria (L.) Druce (Leguminosae), a plant of the Thar Desert of India and Pakistan is used traditionally by local people for the treatment of memory disorders and to arrest wandering of the mind. Objective: The study includes scientific validation of P. cineraria for nootropic activity. To elucidate the possible mechanism, the anticholinesterase activity was also investigated in different parts of the brain. Materials and methods: Methanol extract of P. cineraria stem bark (200, 400 and 600 mg/kg body weight p.o.) was administered once in a day for 7 days to rats and these rats were then subjected to Morris water-maze (MWM) test for spatial reference memory (SRM) and spatial working memory (SWM) versions of memory testing. The inhibitory effect of the extract on acetylcholinesterase (AChE) in discrete rat brain regions (prefrontal cortex [PFC], hippocampus [HIP] and amygdala [AMY]) was also investigated using acetyl thiocholine iodide and dithiobisnitrobenzoic acid reagent. Results and discussion: The oral administrations of methanol extract of P. cineraria in all doses tested, significantly (p < 0.05) improved both spatial reference and working memories in the MWM test in terms of decrease in escape latency during SRM and increase in time spent in the target quadrant during SWM probe trial. A ceiling effect was observed at 400 mg/kg. Pre-treatment for 7 days significantly inhibited the activity of AChE in the HIP, PFC and AMY. Conclusion: The extract exerted significant nootropic activity in the MWM test which may be attributed to the inhibition of brain AChE. © 2012 Informa Healthcare USA, Inc.